Hibah (gift inter vivos) by parent in favour of some children to the exclusion of the others under Islamic Law - Ibrahim, Badruddin (Brill, 2017)
This study examines issues arising from gift giving (hibah) by a parent to one or more of his/her children to the exclusion of the others under Islamic law in general and as applied to Muslims in Malaysia in particular. Does a parent have an absolute right to dispose of property to his/her children by means of hibah without concern for fairness to the other children? Is hibah a valid and acceptable practice in a modern Muslim society? Is the core issue one of an individual’s absolute property rights or is it restrained by the principle of fairness in dealing with properties? This study will attempt to provide a right and acceptable guidance with respect to the disposal of property to children by means of hibah.